Hodnocení závaznosti otresu mozku a poruchy zdraví pomocí monitorování hladin neuron specifické enolázy a proteinu S-100b v séru - Vajtr, D; Průsa, R; Kukacka, J; Houst'ava, L; Sámal, F; Pelichovská, M; Strejc, P; Toupalík, P (Soudni lekarstvi, 2007)
INTRODUCTION: Proteins released to the circulation from affected glial (neuron specific enolasis, NSE) or ganglial cells (S-100b protein) during traumatic brain injury might be used in diagnosis of traumatic brain injury in cases with negative finding on computer tomography scan (concussion) or in patients where the serious clinical status does not corresponde with mild changes on CT scan (diffuse axonal injury, DAI). Classification of DAI according Gennarelli considered the concussion as lower degree of DAI. MATERIALS AND METHOD: 15 patients were divided into group I of mild conccussion (n=3) with 1-day duration of hospitalisation, group II of serious concussion (n=4) with more days duration of hospitalisation with negative findings on CT scan and group III of patients with diagnosis of DAI (n=8). Blood samples were investigated by immunoanalysis for NSE and protein S-100b (Elecsys 2010, Roche). RESULTS: Values of NSE (16.30 +/- 2.33 vs. 110.48 +/- 34.99 vs. 24.07 +/- 6.29 microg/l), and protein S-100b (0.207 +/- 0.03 vs. 0.945 +/- 0.69 vs. 0.736 +/- 0.36 microg/l) overdrow the reference value in cases of group I, II, and III. We discuss the biomechanics of trauma and the blood brain barrier damage in comparison with values of NSE and S-100b protein. CONCLUSION: [corrected] We proved the significantly higher values of the NSE in group of serious concussion compared to group of DAI. We demonstrated that concussions in some cases lead to serious damage of health.
Keywords: Nerve Growth Factors; komoce mozku; S-100 kalcium vázající protein G, podjednotka beta; S100 Calcium Binding Protein beta Subunit; Humans; biologické markery; S100 Proteins; Brain Concussion; neurotrofní faktory; lidé; difuzní axonální poranění; fosfopyruváthydratasa; Biomarkers; Phosphopyruvate Hydratase; Prognosis; prognóza; Diffuse Axonal Injury; proteiny S100